Gastrointestinal, Behaviour and Anxiety Outcomes in Autistic Children Following an Open Label, Randomised Pilot Study of Synbiotics vs Synbiotics and Gut-Directed Hypnotherapy. - Mitchell, Leanne K.; Heussler, Helen S.; Burgess, Christopher J.; Rehman, Ateequr; Steinert, Robert E.; Davies, Peter S.W. (Journal of Autism & Developmental Disorders, 2026)
Alterations of the microbiome-gut-brain (MGB) axis have been associated with autism spectrum disorder (ASD) and disorders of gut-brain interaction (DGBI). DGBI are highly prevalent in autistic children and are associated with worsening behaviour and anxiety. Treatments such as probiotics, prebiotics and gut-directed hypnotherapy (GDH) have shown efficacy in improving gut symptoms in children. The primary objective of the study was to compare changes in gastrointestinal (GI) scores following a 12-week intervention of synbiotics (prebiotic + probiotic) +/- GDH with a follow-up at 24 weeks. Secondary objectives included changes in behavioural and anxiety symptoms, while changes in gut microbiome composition were assessed as an exploratory objective. Children diagnosed with ASD aged 5.00-10.99 years (n = 40) were recruited and randomised (1:1) to a 12-week intervention of either synbiotics (SYN group) or synbiotics + GDH (COM group). Both the SYN and COM group experienced significant reductions in total GI scores post-intervention and at follow-up (p < 0.001), with no superiority of the COM treatment over the SYN treatment. The COM group showed beneficial reductions in anxiety scores (p = 0.002) and irritability behaviours (p < 0.001) which were not present in the SYN group. At follow-up, only those in the COM group maintained significant reductions in GI pain scores (p < 0.001). There were significant changes in gut microbiota such as increases in Bifidobacterium animalis and Dialister in both groups over time. In conclusion, synbiotics with or without GDH may help support standard care for autistic children who suffer comorbid DGBI. The trial was prospectively registered at clinicialtrials.gov on 16 November 2020 (NCTO4639141).